'Addressed to you not as a smoker… but as a doctor': doctor‐targeted cigarette advertisements in JAMA. (7th February 2018) - Jackler, Robert K.; Ayoub, Noel F.
Abstract: Background and aim: During the mid‐20th century tobacco companies placed advertisements in medical journals to entice physicians to smoke their brand and, more importantly, to recommend it to their patients. They have been little studied, in part because advertising sections in medical journals are almost universally discarded before binding. This study aimed to define the themes and techniques used in doctor‐targeted tobacco advertisements that appeared in American medical journals in the mid‐20th century and determine the motivations and tactics of the tobacco industry in engaging the medical profession in this way. Methods: Doctor‐targeted tobacco advertisements from JAMA and the New York State Medical Journal appearing between 1936 and 1953 were studied. These were obtained from the New York Academy of Medicine and the UCSF Truth database of tobacco industry documents. Content analysis of advertising slogans and imagery was conducted. Using internal tobacco industry documents, we examined the relationship between tobacco advertisers and medical journals. Results: Among the 519 doctor‐targeted advertisements, 13 brands were represented, with two (Philip Morris and Camel) accounting for 84%. Correspondence between tobacco advertisers and medical journal editors reveals the potent influence of revenue to the sponsoring society and personal compensation derived from consulting arrangements. Content analysis of the advertisements revealed much flattery of doctors and arguments professing the harmlessness of the company's brand. Conclusions: Analysis of doctor‐targeted tobacco advertisements in American medical journals from 1936 to 1953 suggest that tobacco companies targeted physicians as a potential sales force to assuage the public's fear of health risks and to recruit them as allies against negative publicity. Tobacco companies also appeared to try, through the substantial advertising revenue passed by journals to their parent medical societies, to temper any possible opposition by organized medicine.